Fluorofenidone inhibits apoptosis of renal tubular epithelial cells in rats with renal interstitial fibrosis - Yang,Hui (2019)
This study aimed to investigate the mechanism of fluorofenidone (AKF-PD) in treating renal interstitial fibrosis in rats with unilateral urinary obstruction (UUO). Thirty-two male Sprague-Dawley rats were randomly divided into sham, UUO, UUO + enalapril, and UUO + AKF-PD groups. All rats, except sham, underwent left urethral obstruction surgery to establish the animal model. Rats were sacrificed 14 days after surgery, and serum was collected for renal function examination. Kidneys were collected to observe pathological changes. Immunohistochemistry was performed to assess collagen I (Col I) protein expression, and terminal deoxynucleotidyl transferase-mediated nick end-labeling staining to observe the apoptosis of renal tubular epithelial cells. The expression of Fas-associated death domain (FADD), apoptotic protease activating factor-1 (Apaf-1), and C/EBP homologous protein (CHOP) proteins was evaluated by immunohistochemistry and western blot analysis. AKF-PD showed no significant effect on renal function in UUO rats. The pathological changes were alleviated significantly after enalapril or AKF-PD treatment, but with no significant differences between the two groups. Col I protein was overexpressed in the UUO group, which was inhibited by both enalapril and AKF-PD. The number of apoptotic renal tubular epithelial cells was much higher in the UUO group, and AKF-PD significantly inhibited epithelial cells apoptosis. The expression of FADD, Apaf-1, and CHOP proteins was significantly upregulated in the UUO group and downregulated by enalapril and AKF-PD. In conclusion, AKF-PD improved renal interstitial fibrosis by inhibiting apoptosis of renal tubular epithelial cells in rats with UUO.